Recurrent Pneumococcal Meningitis in Children: A Multicenter Case–control Study. Issue 9 (September 2019) - Darmaun, Laura; Levy, Corinne; Lagrée, Marion; Béchet, Stéphane; Varon, Emmanuelle; Dessein, Rodrigue; Cohen, Robert; Martinot, Alain; Dubos, François
Abstract : Background: Pneumococcal meningitis (PM) is a serious disease that can rarely recur at a later time after the initial episode. Methods: A retrospective multicenter case–control study was conducted with data for children 18 years of age or younger obtained from the National Observatory of Bacterial Meningitis in Children between January 2001 and September 2015. Cases were all patients with RPM. Each case was matched with 2 randomized controls with a single PM episode in the year of the first episode of PM in the case and born the same year. Case and control data were compared. Results: Among the 1634 PM episodes in children 18 years of age or younger, 24 (1.5%) children had RPM. RPM cases were significantly less frequent than single PM cases in winter (27% vs. 48%; P =0.03) and showed significantly less concomitant ear, nose and throat infections when considering the first episode (30% vs. 56%, P = 0.04) and all episodes (28% vs. 56%, P < 0.01). Cerebrospinal fluid leakage was frequent in RPM cases versus controls (83% vs. 10%, P < 0.01), including 25% discovered after the third PM episode. Immune deficiency was absent in cases and present in 15% of controls. Cases and controls did not differ in death rate or neurologic outcome. Conclusions: RPM is rare in children. Cerebrospinal fluid leakage must be considered. Abstract : Supplemental Digital Content is available in the text.